The Evolution of English Stylistics: From Classical to Modern Approaches - Akhmadullina Alina Ildarovna (Western European Studies, 2023)
This study tracks the dynamic transitions from classical to modern approaches by examining the evolution of English stylistics over historical periods. By examining literary works from the Classical, Renaissance, Neoclassical, Romantic, and Modern periods, the study identifies unique stylistic characteristics that are characteristic of each historical period. The analysis shows a shift in rhetorical style from the Classical era's formal eloquence and structured rhetoric to the Renaissance's linguistic inventiveness and flexibility. The Romantic era embraces subjectivity and emotion, while the Neoclassical period emphasizes a return to structured forms. The 20th century sees a shift in language that is centered on structural analysis. Cultural factors become crucial factors that mold the stylistic terrain. The results add to a more complex understanding of how tradition, innovation, and cultural dynamics have interacted throughout English stylistics' development.
Keywords: English Stylistics; Evolution of Stylistics